A semiotic analysis of body positivity in Meghan Trainor’s ‘You Don’t Know Me’: A study on symbolism and representation - Devany, Clayrine; Leiliyanti, Eva; Adha Kurniati, Nurul (Lililacs Journal, 2025)
This study examines the semiotic analysis of body positivity in Meghan Trainor’s music video entitled You Don’t Know Me, by the approach of a study on symbolism and representation, particularly the Roland Bathes’ semiotic sign theory. With that, this study aims to find out the denotative and connotative meanings of the symbols contained in the images and song lyrics of the video clip. The study reveals how Meghan Trainor’s music video challenges conventional beauty norms and promotes body positivity by analyzing its visual and lyrical elements using Roland Barthes’ semiotic theory. The body positivity celebrates the diversity of body types, skin colors and features. After all, this study argues that Trainor’s music video contributes to the body positivity movement and demonstrates how popular media can challenge entrenched beauty myths and foster more inclusive ideals regarding attractiveness and self-worth.